Religious Leaders and Elections in the Polarizing Context of Indonesia - M. Iqbal Ahnaf; Danielle N. Lussier (Humaniora, 2019)
Studies of elections in young democracies point to the risk of elections intensifying existing social conflicts, a process observed in Indonesia in recent years. The 2017 mayoral election in Yogyakarta contradicts this trend, presenting an empirical puzzle. Despite the fact that local conditions might encourage electoral mobilization along sectarian lines, we find evidence of restraint. Based on analysis of the contents of sermons in 12 mosques and churches in the month before the election we identify three factors that discourage religious leaders from exercising opportunities to intensify religious tension. These include (a) elites were not motivated to exacerbate communal tension because they do not feel the election will bring about reform or change that would seriously affect their established position, (b) even though sectarian messaging is possible, the elites did not believe masses could be easily persuaded by sectarian political messaging, and (c) political outbidding by using sectarian messages would risk confronting the local dominant culture of harmony. These findings suggest that several factors need to be activated for religious leaders to exercise their moral authority over worshippers for political purposes. The presence of an opportunity structure for intensifying sectarian conflict is not sufficient for that conflict to emerge.